Nilai Pendidikan Sosial pada Kitab Al-Hikam Karya Ibnu Atha'illah Al-Sakandari - Rizky Habibie; Moh. Syamsul Falah (Menara Tebuireng, 2019)
Sufism and social education cannot be separated because Sufism itself is the knowledge of all forms of behavior of the human soul, both praiseworthy and despicable, then how to rid oneself of despicable deeds and decorate it with the praiseworthy, how to travel the way to Allah and run as fast as possible towards Allah SWT. Human interaction with other parties does not come out of three types of relationships. The focus of this research consists of: 1) What is the value of social education in Al-Hikam?, 2) How is the implementation of the value of social education in Al-Hikam?. To discuss the above research, the literary method is used, this research is a philosophical approach that plays a role in opening up thinking to realize the phenomena behind something that appears and also using another approach, namely the biographical approach that aims to describe the thoughts or views of figures, religious figures, politicians, or historian. The data source is taken from the work of Taj Al-Din Abu Al-Fadl Ahmad bin Muhammad bin Abdul Karim bin Abdul Al-Rahman bin Abdulullah bin Isa bin Al-Husein bin Atha'illah with the title Al-Hikam. In this study, the following results were obtained: 1) Al-Hikam discussed a lot about Sufi Uluhiyah and Insaniyah. Tasawuf insaniyah discusses human nature related to human nature in the world and the hereafter. There is a maqamat that needs to be done to understand about relations with humans; tajrid maqam and asbab maqam. In this station, there needs to be an initial fortification in the form of a strong and straight mental self (riyadlah). And attitudes that can be learned in the book of Al-Hikam by Ibn Atha'illah are sincere, enterprising, tawadlu', friendship, respect for others, fair, and help each other. 2) The implementation of the value of social education in the book Al-Hikam is called suluk education which has two stages in its application, marhalah ta'sis (the phase of strengthening and planting) and marhalah nuwuww (the phase of distribution and development) which at each stage will be given suggestions and provision to make a good characteristic and nature of social education. Both phases will have an impact in critical thinking on the meaning of the relationship to Allah and the relationship to humans